Dynamic analysis and program formalization of regional banks activity in catastrophe theory conception - Alma Obaeva; Vladimir Zaitsev (European Regional Science Association (ERSA), 2001)
Present researches in the framework of catastrophe theory aimed to describe in formalized form the dynamics of regional banks activity in transitive economics. For this purpose the system of differential equations was algorithmically solved and the decision with approximation error in 9.4% gives reliable description of the real statistics of banks activity. Certain managing parameters, establishing the dynamics of money input components interaction and output producing in banks activity were defined and theoretical approach to functional dependencies finding of above mentioned parameters was made. The integral activity curve of the bank was build and it showed the exact time Tx of bifurcation appearance, bringing about the misbalance in banks production with consequence in banks catastrophe. It was found that since the bank integral activity curve had fallen below the zero the bank experienced the "fold" bifurcation, assuming the catastrophe( bankruptcy) and this situation couldn't be diagnosed in time by means of traditional methods of bank analysis. The ways of planning and crisis management in regional politics conception were offered by varying of initial banks inputs and managing parameters.
Keywords: 330